2000
DOI: 10.1152/ajpregu.2000.279.4.r1321
|View full text |Cite
|
Sign up to set email alerts
|

Treadmill running produces both positive and negative physiological adaptations in Sprague-Dawley rats

Abstract: Exercise training produces a vast array of physiological adaptations, ranging from changes in metabolism to muscle mitochondrial biogenesis. Researchers studying the physiological effects of exercise often use animal models that employ forced exercise regimens that include aversive motivation, which could activate the stress response. This study examined the effect of forced treadmill running (8 wk) on several physiological systems that are sensitive to training and stress. Forced treadmill running produced bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
201
3
15

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 270 publications
(231 citation statements)
references
References 49 publications
12
201
3
15
Order By: Relevance
“…Indeed, ACTH upregulates the expression of its own receptors on adrenocortical cells in such a feed-forward manner (21,28). In accordance with this, 2 wk of voluntary wheel running have recently been shown to increase mRNA levels of StAR (25). Alternatively, a recent study has also suggested that enhanced sympathoadrenomedullary activity, found to be associated with exercise training, may positively modulate adrenal sensitivity to ACTH (8).…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…Indeed, ACTH upregulates the expression of its own receptors on adrenocortical cells in such a feed-forward manner (21,28). In accordance with this, 2 wk of voluntary wheel running have recently been shown to increase mRNA levels of StAR (25). Alternatively, a recent study has also suggested that enhanced sympathoadrenomedullary activity, found to be associated with exercise training, may positively modulate adrenal sensitivity to ACTH (8).…”
Section: Discussionmentioning
confidence: 82%
“…In rodents, the effect of exercise on diurnal HPA activity and adrenal sensitivity to ACTH is also unclear. For example, compared with S animals, trained animals have increased resting stress hormones (17,25), while others show similar resting concentrations (14,27) or even decreased resting concentrations (4,7,9,19). It is likely that the variety of training protocols and the varying training durations used, as well as the timing of blood sampling in these rodent studies, contributes to the discrepancies in findings.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…It has been argued that exercise training in and of itself is stressful and therefore caution is advised when interpreting behavioral or endocrine response adaptations (or the lack thereof) to subsequent challenges or stressors, as they could be masked or altered by the chronic stress inherent in the training (Moraska et al 2000;Burghardt et al 2004). Indeed, certain forced exercise training paradigms in controlled animal studies have resulted in physiological adaptations, including adrenal hypertrophy and/or thymic involution, that are typically associated with chronic activation of the HPA-axis system (Selye 1936).…”
Section: Discussionmentioning
confidence: 99%
“…Although the meaning of this behavior is complex, peripheral locomotion is often interpreted as locomotor activity (Ramos et al, 2003;IzĂ­dio et al, 2011). Thus, it can be suggested that the PE-induced increase in cardiovascular or muscular capacity of these animals (Moraska et al, 2000) facilitated locomotion in the OF. Alternatively, the increase in general locomotion may be a result of the selection of animals that completed the treadmill training, i.e., rats with baseline increased locomotion.…”
Section: 3 Statistical Analysismentioning
confidence: 97%